Socialization of Village Management Strategy towards Golden Indonesia - fii, M. Safii Murad Daulay; uswa, Uswatun Hasanah; ayunda, Ayunda Fatmasari; Oppie, Oppie Meisya Tanjung; oki, Oki Prayogi; tina, Hajatina (Outline Journal of Community Development, 2025)
This community service aimed to strengthen village management capacity in facing future development challenges toward Indonesia Emas 2045. The program was carried out by lecturers of the Management Study Program at Universitas Tjut Nyak Dhien together with students, focusing on empowering Amplas Village through socialization activities. The method applied was the delivery of structured materials on strategic planning, implementation, monitoring, and evaluation of village programs, followed by open discussions and interactive sessions with the village head and local community. The results indicated that the socialization successfully enhanced the understanding of village officials and residents about the importance of accountable, participatory, and innovative management. The community showed enthusiasm in exploring opportunities for collaboration, especially in agricultural and livestock development, while the existence of cooperatives was recognized as a key driver of economic empowerment. In conclusion, this activity contributed to increasing public awareness, strengthening governance practices, and providing practical learning for students, thereby fostering synergy between higher education and the community in achieving sustainable village development